Can Compensation Mediate Discipline in Improving the Performance of Government Employees? - Ngatimun, Ngatimun; Musriati, Titik; Hermanto, Hermanto; Sulistyan, Riza Bahtiar (Innovation Business Management and Accounting Journal, 2023)
Performance is the achievement of work results obtained in various ways that are expected in accordance with organizational goals. This study aims to examine the direct and indirect effects of work discipline and compensation on employee performance, work discipline on employee performance through compensation mediation. The research location is in a government agency in Probolinggo Regency. The sample used was 63 people from government agencies. The mediation analysis model uses the Jamovi application. The results showed that compensation was not able to mediate work discipline on employee performance, but compensation was able to have a direct effect on employee performance. Likewise, work discipline can have a direct effect on employee performance so that work discipline has a total positive and significant influence on employee performance after being mediated by compensation. Increasing discipline by paying attention to timeliness of work, increasing work compensation by providing adequate incentives and increasing employee performance by fostering a greater sense of responsibility the goal.